PENDIDIKAN GENDER DALAM PERSPEKTIF ISLAM - kulsum, Ummu (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2014)
Education of Gender is an effort that gives the understanding to woman that education is necessary for her self. Not merely understanding about her self, but woman comprehends men dichotomy and woman in context of sosio cultural which must be fought for. During the time of political world, it is not woman domain, but if that term does not be fought for by woman, hence we will be difficult to fight for that. Because she can comprehend about condition of woman herself. Creation of model and consanquinity system in society take long time, and there are various factors of the condition of objective geography, including ecology. In cross cultural society, pattern determination of burden of gender (assignment gender)has more relation to factor of biology gender. Sighting returns burden of gender unjustly assessed represent heavy duty of mankind. Burden Identification of gender more than simply recognition of genitals.But concerning basal values which are owned in society. Though Islam, position of woman and men are balanced (well-balanced), which differentiate both because of a fear.